Estudos do transcriptoma de sementes de Solanum paniculatum L. submetidas ao déficir hídrico durante a germinação - Silva, Pedro Bento da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Solanum paniculatum L belongs to the Solanaceae family and presents growth and development in unfavorable environmental conditions such as drought and salt stress, acid soils and soils poor in nutrients. Therefore, the objective of this work was to study the S. paniculatum L seed transcriptome induced to tolerate drought stress. The dried seeds were placed in tubes containing 15 mL of PEG 8000 solution with osmotic potential of -0.4; -0.8; -1.0 and -1.2MPa followed by incubation at 15° C for 15 days. Then the seeds were subjected to germinate under drought conditions, which was generated by the use of germination medium containing PEG 8000 solutions at potentials of 0,0, -0,2, -0,4, -0,6, -0, 8 and -1,0 MPa at 25° C under constant light. Following, RNA was extracted and had the quality verified in Bioanalyzer and libraries were prepared using the TruSeq RNA sample prep protocol v2. Sequencing was performed on HiScanSQ (Illumina) and the data generated were analyzed in CLC Genomics Workbench platform version 6.0.2 (CLC bio, Denmark). The contigs were recorded using Blast2go program and functional enrichment for GO and Bingo. We observed an increase in the percentage of germination under drought stress of seeds previously subjected to PEG treatment (-1,0MPa) in comparison with seeds that were not treated. There were generated 34.640 transcripts, where 208 were differentially expressed but only 102 transcripts where associated with stress. However, only twenty three transcripts have known function which are associated with response to stress (drought, heat and oxidative stress). Among those, thirteen genes had the expression validated by qPCR. Here, we discuss the possible involvement on these genes on stress tolerance in Solanum paniculatum seeds during germination.

A planta de Solanum paniculatum pertence à família Solanaceae e apresenta crescimento e desenvolvimento em condições ambientais desfavoráveis, tais como estresse hídrico e salino, solos ácidos e solos com deficiência em nutrientes. Por tanto, o objetivo deste trabalho foi estudar o transcriptoma de sementes de S. paniculatum L induzidas a tolerar déficit hídrico. As sementes secas foram acondicionadas em tubos contendo 15 mL de solução de PEG 8000 com potencial osmótico de -0,4; -0,8; -1,0 e - 1,2MPa e mantidas à temperatura de 15 °C durante 15 dias. Em seguida, as sementes foram colocadas para germinar em condições de déficit hídrico, que foi realizado pelo uso de meio germinativo contendo soluções de PEG 8000 nos potenciais de 0,0, -0,2, - 0,4, -0,6, -0,8 e -1.0 MPa na temperatura de 25 °C e luz constante. Após a conclusão dessa etapa, o melhor tratamento (-1,0 MPa) foi utilizado para os estudos moleculares. Posteriormente, foi extraído o RNA total das sementes condicionadas e não condicionadas (NC). Em seguida a integridade do RNA foi verificada em Bioanalyzer e as bibliotecas foram preparadas utilizando o protocolo TruSeq RNA sample prep v2. O sequenciamento foi realizado no HiScanSQ (Illumina) e os dados gerados analisados pela plataforma CLC Genomics Workbench versão 6.0.2 (CLC bio, Denmark). Os contigs foram anotados usando o programa Blast2go e o enriquecimento funcional pelo GO e Bingo. Os genes diferencialmente obtidos foram validados via RT-qPCR. Observou-se aumento na porcentagem de germinação total das sementes condicionadas (-1,0 MPa) em relação às não condicionadas (NC). Foram gerados 34.640 transcritos, onde 208 transcritos foram diferencialmente expressos, porém, 23 apresentaram respostas a estresse em sementes de S. paniculatum L, associados com estresse abiótico (déficit hídrico, estresse térmico e... (Resumo completo, clicar acesso eletrônico abaixo)
Studies of the transcriptome of Solanum paniculatum L. seeds submitted to water deficit during germination
Keywords: Differential expression; RNA-Seq; Priming; Induced tolerance; Estatistica - Analise; Acido ribonucleico; Desidratação (Hídrica); Genética vegetal; Germination